Bacterial community shift and antibiotics resistant genes analysis in response to biodegradation of oxytetracycline in dual graphene modified bioelectrode microbial fuel cell. (March 2019) - Chen, Junfeng; Yang, Yuewei; Liu, Yanyan; Tang, Meizhen; Wang, Renjun; Tian, Yuping; Jia, Chuanxing
Graphical abstract: Highlights: OTC biodegradation mechanisms discussed by bacterial community shift and ARGs. Proteobacteria enriched in O-GM-BA, Proteobacteria, Bacteroidetes riched in O-GM-BC. Salmonella, Geobacter contributed to OTC biodegradation and EET process in O-GM-BA. Abundant degrading bacteria ( Moheibacter etc. ) were enriched in O-GM-BC. Coding genes of efflux pump, ribosome protective protein, modifying were detected. Abstract: This study explored the biodegradation mechanisms of oxytetracycline (OTC/O) and electrochemical characteristics from the perspective of bacterial community shift and OTC resistance genes in dual graphene modified bioelectrode microbial fuel cell (O-D-GM-BE MFC). In phylum level, Proteobacteria was accounted to 95.04% in O-GM-BA, Proteobacteria and Bacteroidetes were accounted to 59.13% and 20.52% in O-GM-BC, which were beneficial for extracellular electron transport (EET) process and OTC biodegradation. In genus level, the most dominant bacteria in O-GM-BA were Salmonella and Trabulsiella, accounting up to 83.04%, moreover, representative exoelectrogens ( Geobacter ) were enriched, which contributed to OTC biodegradation and electrochemical performances; abundant degrading bacteria ( Moheibacter, Comamonas, Pseudomonas, Dechloromonas, Nitrospira, Methylomicrobium, Pseudorhodoferax, Thiobacillus, Mycobacterium ) were enriched in O-GM-BC, which contributed to the maximum removal efficiency of OTC; coding resistance genes of efflux pump, ribosome protective protein and modifying or passivating were all found in O-GM-BE, and this explained the OTC removal mechanisms from gene level.